Congenital Complete Heart Block in Fetal Echocardiography - Singh, Amit Kumar; Rajak, Brijmohan; Singh, Ruby; Mandal, Jitendra (Nepalese Heart Journal, 2021)
Congenital Complete Heart Block (CHB) in a fetus is a rare diagnosis occurring 1 in 15,000 to 20,000 live births which can be diagnosed by echocardiography. It’s less talked disease. It is uncommonly reported even in countries where fetal echocardiography is performed in much higher numbers. For countries like Nepal, where small number of fetal echocardiography is performed, we present a case of lupus as the cause of congenital CHB.